EVALUASI HASIL PEMBELAJARAN PENJAS PADA SUB TEMA SEPAK BOLA DI SD N 53 BANDA ACEH - Arisman, Arisman; Jalaluddin, Jalaluddin; Boihaqi, Boihaqi (Jurnal Seramoe Education, 2025)
This study aims to evaluate student learning outcomes in football learning at SD Negeri 53 Banda Aceh, especially in grade 5 students, using a qualitative research approach. The research method used is a case study, focusing on an in-depth understanding of students' experiences and perceptions of football learning. Data is collected through participatory observation during the learning process, in-depth interviews with students, and analysis of documents such as lesson notes and skills test results. The triangulation approach is used to verify and test the validity of the data. Data analysis shows that grade 5 students at SD Negeri 53 Banda Aceh have experienced significant improvement in their understanding of the basic techniques of the football game. Factors such as the presence of supportive teachers, social interaction between students, and their intrinsic motivation play a crucial role in improving their learning. The results of this study describe several challenges faced in learning football in the school, including limited resources and adequate facilities. Suggestions for improvement include increased training for physical teachers, further development of a sports curriculum that includes football, as well as closer collaboration between schools and parents in supporting extracurricular learning. This research is expected to provide in-depth insights into how football learning can be improved at SD Negeri 53 Banda Aceh, as well as providing a foundation for the development of more effective learning strategies in sports in elementary schools, then it is an important factor that must be known by teachers, especially PJOK teachers in order to better understand the condition of students when they are doing, The process of dissemination is to provide spirit to students in presenting the material to be learned so that students can adjust their conditions and abilities. So that the student can be confident during the learning process.